PENGETAHUAN DAN PERILAKU IBU TENTANG ASI EKSKLUSIF PADA BAYI 0-6 BULAN DI WILAYAH KERJA PUSKESMAS TANJUNG UBAN KECAMATAN BINTAN UTARA KEPULAUAN RIAU - Riris Oppusunggu; Rostalam Murni Simatupang (POLTEKKES KEMENKES MEDAN, 2021)
Breastmilk provision to babies from birth to age 6 months (exclusive breast milk) is the best food for babies. Considering the importance of exclusive breastfeeding itself is not balanced with the correct breastfeeding, UNICEF said that the mother's ignorance of the importance of exclusive breastfeeding, the right way to breastfeed babies, as well as marketing launched aggressively by formula milk, it is an inhibiting factor for the formation of parental awareness in providing parents exclusive breastfeeding. The purpose of this study was to determine the description of maternal knowledge and behavior about exclusive breastfeeding in infants of 0-6 months in the working area of ??the tanjung uban community health care of Bintan Utara in Riau islands.This research was conducted in the working area of ??Tanjung Uban community health center, Bintan Utara Islands, Riau Islands, when the data was collected in February 2020. This research was observational. The population in the study were all breastfeeding mothers who had 0-6 months of infants totaling 91 people. The sample in this research was part of the population. The sample was selected with the criteria of a village close to the Tanjung Uban community health center in Bintan Utara Islands, Riau Islands with a total sample of 45 infants aged 0-6 months.The results of the study illustrate the level of knowledge of respondents in either category as many as 9 people (20%) enough categories of 15 people (33.4%) while 21 people (46.5%) in less category. The description of the level of behavior of respondents in the good category of 7 people (15.6%) enough categories of 14 people (31.1%) while 7 people (53.3%) in the less category. Samples who did not get exclusive breastfeeding were 36 people (80%) while those who received exclusive breastfeeding were only 9 people (20%).